Hydrogen production from urea in human urine using segregated systems. (15th August 2022) - Asiain-Mira, Ruben; Smith, Collin; Zamora, Patricia; Monsalvo, Victor M.; Torrente-Murciano, Laura
Abstract: Removal of nitrogen compounds through biological processes represents the highest energy consumption in conventional centralised wastewater treatment facilities. Alternatively, segregated systems, where wastewater is treated at its source, present the potential to provide value to nitrogen-rich compounds contained in wastewater like urea. This paper demonstrates the feasibility of a novel process to recover energy from human urine based on the pre-isolation of urea to decrease the energy requirements for its thermal decomposition compared to the conventional thermal treatment when in solution, followed by its decomposition into hydrogen. Herein, urea is separated from an aqueous solution by adsorption onto activated carbon. Thermal urea desorption and decomposition into ammonia and CO2 at 250 °C leads to full regeneration of the carbon, showing a constant adsorption capacity for at least 5 consecutive adsorption/desorption cycles. Finally, when the regeneration and urea decomposition step is coupled to an ammonia decomposition catalyst, hydrogen is produced to be used as an energy fuel. This process opens the door to a new way of circular economy by energy recovery from hydrogen-rich components in segregated wastewater streams. Preliminary energy balances show that the adoption of this energy recovery system in a city of 160, 000 inhabitants would lead to a daily hydrogen production of 430 kg, with a net energy production of 2, 500 kWh/day. In addition, such waste-to-energy process would lead to energy savings of 4, 600 kWh/day in a conventional wastewater treatment plant reducing its energy consumption by around 35%. Graphical abstract: Image, graphical abstract